Draft Genome Assembly of the Freshwater Apex Predator Wels Catfish (Silurus glanis) Using Linked-Read Sequencing - Mikhail Yu. Ozerov; Martin Flajšhans; Kristina Noreikiene; Anti Vasemägi; Riho Gross (Oxford University Press, 2022)
The wels catfish (Silurus glanis) is one of the largest freshwater fish species in the world. This top predator plays a key role in ecosystem stability, and represents an iconic trophy-fish for recreational fishermen. S. glanis is also a highly valued species for its high-quality boneless flesh, and has been cultivated for over 100 years in Eastern and Central Europe. The interest in rearing S. glanis continues to grow; the aquaculture production of this species has almost doubled during the last decade. However, despite its high ecological, cultural and economic importance, the available genomic resources for S. glanis are very limited. To fulfill this gap we report a de novo assembly and annotation of the whole genome sequence of a female S. glanis. The linked-read based technology with 10X Genomics Chromium chemistry and Supernova assembler produced a highly continuous draft genome of S. glanis: ∼0.8Gb assembly (scaffold N50 = 3.2 Mb; longest individual scaffold = 13.9 Mb; BUSCO completeness = 84.2%), which included 313.3 Mb of putative repeated sequences. In total, 21,316 protein-coding genes were predicted, of which 96% were annotated functionally from either sequence homology or protein signature searches. The highly continuous genome assembly will be an invaluable resource for aquaculture genomics, genetics, conservation, and breeding research of S. glanis.